Chromosome-level genome assembly and annotation of the maize weevil (Sitophilus zeamais Motschulsky) - Yueliang Bai; Fangfang Zeng; Meng Zhang; Chao Zhao; Shuai Pang; Guiyao Wang (Scientific Data)
Abstract The maize weevil, Sitophilus zeamais Motschulsky, is one of the most destructive pests of stored grains worldwide, posing a significant threat to global food security. To better understand the biology, resistance mechanism, and adaptive evolution of this species, we presented a high-quality chromosome-level genome assembly of S. zeamais using PacBio sequencing and Hi-C technologies. The size of the final assembled genome was 693.21 Mb with scaffold N50 of 61.03 Mb, and 631.97 Mb were successfully anchored into 11 pseudochromosomes. In total, 15,161 protein-coding genes were annotated, of which 98.89% obtained functional descriptions. Additionally, 377.50 Mb of sequences were identified as repeat elements, accounting for 54.46% of the genome. BUSCO analysis revealed a high level of completeness in both the genome assembly and annotation, with scores of 98.17% and 97.22%, respectively. The chromosome-level genome of S. zeamais provides valuable genomic insights that deepen our understanding of the evolution and ecology of Sitophilus species, while also contributing to the development of targeted and innovative control strategies for stored-product pests.